2016
DOI: 10.18632/oncotarget.9499
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical efficacy and synergistic potential of the MDM2-p53 antagonists, Nutlin-3 and RG7388, as single agents and in combined treatment with cisplatin in ovarian cancer

Abstract: Ovarian cancer is the fifth leading cause of cancer-related female deaths. Due to serious side effects, relapse and resistance to standard chemotherapy, better and more targeted approaches are required. Mutation of the TP53 gene accounts for 50% of all human cancers. In the remaining malignancies, non-genotoxic activation of wild-type p53 by small molecule inhibition of the MDM2-p53 binding interaction is a promising therapeutic strategy. Proof of concept was established with the cis-imidazoline Nutlin-3, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 42 publications
3
39
0
1
Order By: Relevance
“… found SAL‐induced inhibition of mTOR pathway in bladder cancer cells while minimal effect on the growth of non‐malignant bladder cell line was observed. As shown in our experiments, CDDP can arrest both sensitive A2780 as well as resistant A2780/CP cells in G2/M phase of cell cycle what is in line with findings of several reports published on various human ovarian carcinoma cells . This CDDP‐induced G2/M phase arrest was accompanied by increased level of DNA damage manifested as the reduced migration of DNA into the tails of comets observed by us in the present investigation, by Hunakova et al .…”
Section: Discussionsupporting
confidence: 93%
“… found SAL‐induced inhibition of mTOR pathway in bladder cancer cells while minimal effect on the growth of non‐malignant bladder cell line was observed. As shown in our experiments, CDDP can arrest both sensitive A2780 as well as resistant A2780/CP cells in G2/M phase of cell cycle what is in line with findings of several reports published on various human ovarian carcinoma cells . This CDDP‐induced G2/M phase arrest was accompanied by increased level of DNA damage manifested as the reduced migration of DNA into the tails of comets observed by us in the present investigation, by Hunakova et al .…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly and in contrast to the experience with doxorubicin, colon cancer cells did not develop acquired-resistance to SYNAP, thus avoiding the drug resistance feature displayed by many chemotherapeutic agents in cancer cells. Also, although cancer cells resistant to one drug can exhibit cross-resistance to other drugs (Zanjirband et al, 2016;Lopez and Banerji, 2017), in our work, doxorubicin-resistant cells showed no cross-resistance to SYNAP. Indeed, SYNAP was able to resensitize doxorubicin-resistant colon cancer cells to the effect of doxorubicin, leading to a marked reduction in its effective dose.…”
Section: Discussionmentioning
confidence: 47%
“…As a critical negative regulator of p53 which is a key regulator of cell cycle checkpoints, MDM2 overexpression decreases p53 protein levels and function leading to accelerated tumor formation and progression [34]. Recent investigations have identified MDM2 is amplified in a variety of human tumours of diverse tissue origins including non-small cell lung cancer, ovarian carcinoma, prostate cancer, and glioblastoma [35][36][37][38]. MDM2 protein levels and activity are regulated by various oncogenic and tumor suppressive pathways [39].…”
Section: Discussionmentioning
confidence: 99%